2002
DOI: 10.1017/s0954579402004029
|View full text |Cite
|
Sign up to set email alerts
|

Can prevention trials test theories of etiology?

Abstract: This paper addresses the issue of whether prevention research methods, particularly those involving randomized prevention trials, can be used to test theories concerning the etiology of psychopathology. Based on recent empirical and theoretical work in developmental psychopathology, three aspects of etiologic theory are discussed: risk and protective mechanisms, the integration of environmental and genetic factors, and patterns of developmental progression in psychopathology across the life span. It is suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 14 publications
0
81
0
3
Order By: Relevance
“…Finally, nesting such preventive intervention programs in a randomized controlled study design may provide us with the critical test of the suggested links between children's social experiences and their executive functions development found by the studies in this special section. Indeed, despite the strengths of the longitudinal designs used, a necessary step in our knowledge on this would be to study using experiments whether the impact of social experiences on children's executive functions is mitigated when prevention is successful in minimizing children's exposure to adverse school social experiences (Howe, Reiss, & Yuh, 2002;Rutter, 2002Rutter, , 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, nesting such preventive intervention programs in a randomized controlled study design may provide us with the critical test of the suggested links between children's social experiences and their executive functions development found by the studies in this special section. Indeed, despite the strengths of the longitudinal designs used, a necessary step in our knowledge on this would be to study using experiments whether the impact of social experiences on children's executive functions is mitigated when prevention is successful in minimizing children's exposure to adverse school social experiences (Howe, Reiss, & Yuh, 2002;Rutter, 2002Rutter, , 2003.…”
Section: Resultsmentioning
confidence: 99%
“…18,74 However, caution should be exercised when making claims about etiologic theory from prevention interventions. 75 It may have been that the impact on body dissatisfaction was not large enough to translate into an effect on bulimic symptoms or that the time frame assessed was not long enough for this to occur. Also, as with appearance teasing, a lack of impact may have been the result of a floor effect, as both groups demonstrated means no higher than 11.72, when the possible range for the scale was 7-42.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the importance to study correlates and predictors of tobacco use at an early age, our results contribute to the identification of adolescents at risk. Second, the possibility exists that our study omitted important mediating variables on our outcome [54] . For instance, other externalizing behavior such as childhood aggression and conduct disorder co-occur with symptoms of ADHD [55] and may be related to tobacco smoking as well.…”
Section: Limitationsmentioning
confidence: 99%